Virtual and mobile healthcare breakthroughs in research and practice (Medical Information Science Reference, 2020)
"This book explores the trends, challenges, and issues related to the emergence of mobile and virtual healthcare. The book also examines how mobile technologies can best be used for the benefit of both doctors and their patients"--Provided by publisher.